Heterologous over-expression of ACC SYNTHASE8 (ACS8) in Populus tremula x P. alba clone 717-1B4 results in elevated levels of ethylene and induces stem dwarfism and reduced leaf size through separate genetic pathways - Plett, Jonathan M.; Williams, Martin; LeClair, Gaetan; Regan, Sharon; Beardmore, Tannis (Frontiers in Plant Science, 2014)
Plant height is an important agronomic and horticultural trait that impacts plant productivity, durability and esthetic appeal. A number of the plant hormones such as gibberellic acid (GA), auxin and ethylene have been linked to control of plant architecture and size. Reduction in GA synthesis and auxin transport result in dwarfism while ethylene may have a permissive or repressive effect on tissue growth depending upon the age of plant tissues or the environmental conditions considered. We describe here an activation-tagged mutant of Populus tremula x P. alba clone 717-1B4 identified from 2000 independent transgenic lines due to its significantly reduced growth rate and smaller leaf size. Named dwarfy, the phenotype is due to increased expression of PtaACC SYNTHASE8, which codes for an enzyme in the first committed step in the biosynthesis of ethylene. Stems of dwarfy contain fiber and vessel elements that are reduced in length while leaves contain fewer cells. These morphological differences are linked to PtaACS8 inducing different transcriptomic programs in the stem and leaf, with genes related to auxin diffusion and sensing being repressed in the stem and genes related to cell division found to be repressed in the leaves. Altogether, our study gives mechanistic insight into the genetics underpinning ethylene-induced dwarfism in a perennial model organism.